Illawarra Folk Festival - Illawarra Folk Club.; Illawarra Folk Festival ([Illawarra, NSW : The Illawarra Folk Club], 2002)
Title from title screen (viewed Sept. 16, 2002)
Web site of the Illawarra Folk Club, featuring the Illawarra Folk Festival. Includes program, folk concerts, newsletter, products, history, contacts and links.
Mode of access: World Wide Web. Available at: http://www.illawarrafolkclub.org.au
Selected for archiving
Keywords: Festivals -- New South Wales -- Illawarra -- Periodicals; Folk festivals -- New South Wales -- Periodicals; Folk music -- New South Wales -- Periodicals; Illawarra Folk Club -- Periodicals; Illawarra (N.S.W.) -- Periodicals